The Influence of the Number of Banks, Distribution of Funds, and Sources of Funds on the Performance of Commercial Banks in Indonesia - Aziz, Khalid Fauzi; Handoyo, Ugroseno Damara Prasadhana; Nur Indra, Muksin (Universitas Gorontalo, 2025)
This research aims to determine the impact of the number of banks, distribution of funds, and sources of funds on the general performance of banks in Indonesia. The location of this research is Indonesia. The object of this research is to collect data on the number of banks, distribution of funds, sources of funds, and performance of commercial banks in Indonesia, taken from the Central Statistics Agency website during 2018–2022. The data analysis method used is the multiple linear regression test using the classical assumption test, regression testing, and hypothesis testing. Based on the research results, it can be explained: 1) Partially, the number of banks does not influence but is significant on bank performance (-3.333 2.110; 0.004 0.05), the distribution of funds does not influence and is not substantial on bank performance (-1.992 2.110; 0.5063 0.05), and the source of funds influences and is significant on bank performance (3,440 2,110; 0.003 0.05); 2) Simultaneous positive and significant influence of the number of banks, distribution of funds, and sources of funds on performance (17.113 2.96; 0.000 0.05; 3) The bank performance variable has no relationship with the variable number of banks, distribution of funds with the figures shown being -0.753, -0.482 and has a relationship to the source of funds of 0.501